Influence of bias magnetic field on the vacuum arc in double‐break vacuum circuit breakers. Issue 4 (14th February 2018) - Liao, Minfu; Qiao, Shuzhen; Lu, Gang; Ge, Guowei; Zou, Jiyan
Abstract : When double‐break vacuum circuit breakers (VCBs) interrupt the fault current, the series arc will generate their individual magnetic fields in different breaks. The magnetic field in one break will influence the arc in another break if the magnetic field is strong enough or the two breaks are very close. In this case, an interactive magnetic field effect happens. This field is also called the bias magnetic field (BMF). BMF can cause anode erosion and affect the performance at current zero. The distribution of BMF and the optimal configuration of the double‐break VCBs were obtained by the electromagnetic field simulation using the Ansoft Maxwell software. Based on the simulated magnetic field data, in the experiments, the interaction between the series vacuum arcs in double‐break VCBs was equivalent to the interaction between a single vacuum arc and the magnetic field generated by a Helmholtz coil. A high‐speed CMOS camera was used to record the trajectory of the vacuum arc plasma under different BMFs with different types of contacts. The results show the BMF can increase the arc voltage, and the arc becomes unstable. When the BMF becomes stronger, the arc voltage increases, and the arc becomes more unstable. In addition, for different types of contacts, the development process of the arc and the influence level are different under the same BMF. For a Wan‐type transverse magnetic field (TMF) contact or strong BMF, metal sputtering is evident and anode erosion becomes serious. For a cup‐type axial magnetic field (AMF) contact, the influence of BMF on the series arc plasma in double‐break VCBs is less than that of the Wan‐type TMF contact. The results of this work may be helpful for the design of compact double‐break VCBs.